The importance of the use of the ESL/EFL websites by advanced English I students from the Foreign Language Department at the University of El Salvador in the development of their listening skill during the term II- 2012 - Huezo Sánchez, Karla Lesslye; López Ramos, Claudia Yamilet; Renderos Santana, Ana Evelyn; Henríquez Pacas, Nelda María Yvette; Garay Salinas, Ricardo (San Salvador,El Salvador : Universidad de El Salvador, 2012)
The purpose of this research is to report on the importance of the use of EFL/ESL websites in the development of the listening skill in the students of the Advanced English Level at the University of El Salvador. Taking into account that generally students agree that listening is the most difficult skill to develop since it is the one that they hardly ever practice outside of the classroom, this study investigated such importance of the use of ESL/EFL websites as a mean to develop the listening skill. It evaluated a group of forty students, which were enrolled in the Advanced English I level at the Foreign Language Department in the University Of El Salvador, during the semester II, 2012. The students were introduced to five websites and instructed to use them, to practice their listening skill outside of the classroom periodically. The data collected revealed that despite some difficulties encountered, students had an overall positive attitude towards using the selected websites in the development of their listening skill. Besides, students found that practicing English to develop their listening skill through ESL/EFL websites was interesting and effective in the development of their listening skill.
Anexos.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Bibliografía : hojas 48-50
Keywords: Inglés -- Enseñanza; EFL; ESL